THE IMPLICATIONS OF SUSTAINABILITY & CLIMATE-RELATED REPORTING, ESG RISK, AND GREEN ACCOUNTING IN ACHIEVING SUSTAINABLE GROWTH - Annisa, Siti Nur; Saputri Mashuri, Ayunita Ajengtiyas (Faculty of Economics and Business University of Mataram, 2024)
The issue of extreme increases in climate change is currently searching for who should be held responsible for the resulting losses. The world is asking for corporate accountability, which is considered a contributor to this increase in climate change. This study was conducted to determine how much influence the company has in reporting and managing its environmental, social and governance aspects seen from sustainability reporting, climate change reporting, unmanaged ESG risk, and green accounting on sustainable growth in companies listed on the Indonesia Stock Exchange in 2022. This study uses secondary data obtained from sustainability reports and financial reports of each company. The number of samples used was 79 companies represented by each sector based on the IDX Industrial Classification for the period 2022. The sampling technique used was non-purposive sampling with multiple linear regression analysis methods. The results showed that (1) Sustainability Reporting has no significant effect on Sustainable Growth, (2) Climate Change Reporting has no significant effect on Sustainable Growth, (3) Unmanaged ESG Risk has a significant positive effect on Sustainable Growth, and (4) Green Accounting has a significant negative effect on Sustainable Growth.